8x-10 = 9-5x
Therefore:
8x + 5x = 9 + 10
13x = 19
x = 1 6/19.
To solve we moved the x's to one side of the equation and the numbers (constants) to the other side. Then we could simplify to solve for the value of x.
95x?d/dx(au)=au*ln(a)*d/dx(u)d/dx(95x)=95x*ln(9)*d/dx(5x)-The derivative of 5x is:d/dx(cu)=c*du/dx where c is a constantd/dx(5x)=5*d/dx(x)d/dx(95x)=95x*ln(9)*(5*d/dx(x))-The derivative of x is:d/dx(x)=1x1-1d/dx(x)=1*x0d/dx(x)=1*(1)d/dx(x)=1d/dx(95x)=95x*ln(9)*(5*1)d/dx(95x)=95x*ln(9)*(5)-95x can simplify to (95)x, which equals 59049x.-ln(9) can simplify to ln(32), so you can take out the exponent to have 2ln(3).d/dx(95x)=59049x*2ln(3)*(5)d/dx(95x)=10*59049x*ln(3)
Do not write an equation in words!!! What does x mean in 10y = 5x + 95x? It is a place holder for a number. Any number.
95x 69 is equal to 6,555.
95x is the same as 95x1, so multiply the 95 and the 1 and reduce the 1 by 1 and you get 95x0. x0 = 1 so your answer is 95.
y=.95x
95x.98mmx46
3x+y=-1 y=-1-3x5x-y=9 5x-(-1-3x)=95x+1+3x=98x=8x=1y=-1-3(1)y=-4(1,-4)
f =95c + 32f =95X 10 + 32=50
950
1(95-x)=70 95x=70 x 25x
3x + 5x + 10 = 0a = 3, b = 5, c = 10D = b - 4ac = 25 - 120 = -95Since D < 0, we have two conjugate complex roots.√D = √-95 = i√95x = (- b ± √D)/2ax = -5/6 + [(√95)/6]i or x = -5/6 -[(√95)/6]i
25x?d/dx(au)=au*ln(a)*d/dx(u)d/dx(25x)=25x*ln(2)*d/dx(5x)-The derivative of 5x is:d/dx(cu)=c*du/dx where c is a constantd/dx(5x)=5*d/dx(x)d/dx(25x)=95x*ln(2)*(5*d/dx(x))-The derivative of x is:d/dx(x)=1x1-1d/dx(x)=1*x0d/dx(x)=1*(1)d/dx(x)=1d/dx(25x)=25x*ln(2)*(5*1)d/dx(25x)=25x*ln(2)*(5)-25x can simplify to (25)x, which equals 32x.d/dx(95x)=32x*ln(2)*(5)